Financial Ratio, Reputation of Public Accountant Office and The Timeliness of Audited Financial Statements - Hernugraheni, Citra; Sukesti, Fatmasari; Santoso, R Ery Wibowo Agung; Khasanah, Lukluul; Nugroho, Wawan Sadtyo; Setyono, Didi; Fakhruddin, Iwan (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
Financial reports provide information needed when making decisions that act as intermediaries for financial transmission and measurement. If the company is late in sending the requested report, it will get a warning. The purpose of this study was to examine the effect of firm size, profitability, solvency, and KAP reputation on audit delay. The population and sample used in this research are 26 food and beverage manufacturing companies in 2019–2021. Using a sampling technique that is purposeful sampling with secondary data types The tool used to test this research uses SPSS 26. The results of the study state that company size has a negative effect on audit delay. Solvency has a positive influence on audit delays. Profitability and reputation of the public accounting firm have no effect on audit delay.